2018
DOI: 10.1007/s12024-018-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of mycobacterium tuberculous coronary arteritis and thrombosis resulting in acute myocardial infarction

Abstract: Tuberculosis (TB) is a prevalent infection worldwide and an endemic infection in Singapore. The most common presentation is that of pulmonary tuberculosis. Extra pulmonary tuberculosis usually involves the lymph nodes, pleura, central nervous system, or abdominal cavity. Involvement of the heart is rare (0.14-2% of TB cases), and when it is involved, it tends to be in the pericardium or myocardium. Here, a rare case of sudden death due to tuberculous coronary arteritis with tuberculous coronary thrombosis resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
8
0
2
Order By: Relevance
“…Likewise, patients with TB have an increased risk of ischemic 9 , 10 , but not hemorrhagic stroke in the first three years after TB diagnosis 10 when compared to non-infected controls. Multiples cases of TB causing coronary arteritis and subsequent AMI have been reported 40 , 41 . Preclinical studies have shown that mycobacterial infection aggravates atherosclerosis formation in the aortas of hyperlipidemic, lipoprotein receptor knockout ( Ldlr −/− ) mice 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, patients with TB have an increased risk of ischemic 9 , 10 , but not hemorrhagic stroke in the first three years after TB diagnosis 10 when compared to non-infected controls. Multiples cases of TB causing coronary arteritis and subsequent AMI have been reported 40 , 41 . Preclinical studies have shown that mycobacterial infection aggravates atherosclerosis formation in the aortas of hyperlipidemic, lipoprotein receptor knockout ( Ldlr −/− ) mice 42 .…”
Section: Discussionmentioning
confidence: 99%
“…3 The heart is involved only in 0.14-2% of all the TB cases, and it tends to affect the pericardium or the myocardium primarily. 7 TB myocarditis was first reported in 1664 by Maurocordat. 8 Cardiac TB can be morphologically categorized into three types: diffuse infiltrative, miliary, and tuberculomas.…”
Section: Discussionmentioning
confidence: 99%
“…8 Cardiac TB can be morphologically categorized into three types: diffuse infiltrative, miliary, and tuberculomas. 7 Rose et al 5 did an extensive study on 19 cases of cardiac TB, and every case demonstrated either miliary or systemic TB. The authors were convinced with three possible routes of spread to the myocardium: directly from the pleural cavity or the pericardium, spread from lymph nodes, and hematogenous dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, patients with TB have an increased risk of ischemic 9,10 , but not hemorrhagic stroke in the rst three years after TB diagnosis 10 when compared to non-infected controls. Multiples cases of TB causing coronary arteritis and subsequent AMI have been reported 33,34 . Preclinical studies have shown that mycobacterial infection aggravates atherosclerosis formation in the aortas of hyperlipidemic, lipoprotein receptor knockout (Ldlr -/-) mice.…”
Section: Discussionmentioning
confidence: 99%